2019
DOI: 10.1016/j.jcf.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3 study of tezacaftor in combination with ivacaftor in children aged 6 through 11 years with cystic fibrosis

Abstract: Background: Tezacaftor/ivacaftor is a new treatment option in many regions for patients aged ≥12 years who are homozygous (F/F) or heterozygous for the F508del-CFTR mutation and a residual function (F/RF) mutation. This Phase 3, 2-part, open-label study evaluated the pharmacokinetics (PK), safety, tolerability, and efficacy of tezacaftor/ivacaftor in children aged 6 through 11 years with these mutations. Methods: Part A informed weight-based tezacaftor/ivacaftor dosages for part B. The primary objective of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 16 publications
6
35
0
1
Order By: Relevance
“…In 2018, the FDA and the EMA approved the cotreatment with tezacaftor/ivacaftor (Symdeko ® or Symkevi ® , Vertex Pharmaceuticals) for patients aged ≥12 years who are F508del-homozygous or F508del-heterozygous with a residual function mutation in trans ( Table 3). In following phase III clinical trials, co-treatment of tezacaftor/ivacaftor was demonstrated to reduce sweat chloride concentration and preserve lung function with relatively low respiratory symptom burden (Walker et al, 2019). Such findings served as basis for the extended approval of tezacaftor/ivacaftor for patients aged ≥6 years.…”
Section: Correctors: Rescuing the Protein Folding Processing And Trmentioning
confidence: 94%
“…In 2018, the FDA and the EMA approved the cotreatment with tezacaftor/ivacaftor (Symdeko ® or Symkevi ® , Vertex Pharmaceuticals) for patients aged ≥12 years who are F508del-homozygous or F508del-heterozygous with a residual function mutation in trans ( Table 3). In following phase III clinical trials, co-treatment of tezacaftor/ivacaftor was demonstrated to reduce sweat chloride concentration and preserve lung function with relatively low respiratory symptom burden (Walker et al, 2019). Such findings served as basis for the extended approval of tezacaftor/ivacaftor for patients aged ≥6 years.…”
Section: Correctors: Rescuing the Protein Folding Processing And Trmentioning
confidence: 94%
“…Thus, initiating CFTR modulator therapy early in life is expected to prevent or reduce the progression of irreversible destruction of the lungs and pancreas in pwCF. Recently, the pharmacokinetics (PK), safety, and tolerability of tezacaftor/ivacaftor were evaluated in a Phase 3, single-group, clinical study of participants 6 through 11 years of age with CF with F/F or F /RF genotypes [16] . That study identified weight-based tezacaftor/ivacaftor dosing regimens in this age group that were generally safe and well tolerated and improved CFTR function as assessed by reductions in sweat chloride (SwCl) concentration [16] .…”
Section: Article In Pressmentioning
confidence: 99%
“…Recently, the pharmacokinetics (PK), safety, and tolerability of tezacaftor/ivacaftor were evaluated in a Phase 3, single-group, clinical study of participants 6 through 11 years of age with CF with F/F or F /RF genotypes [16] . That study identified weight-based tezacaftor/ivacaftor dosing regimens in this age group that were generally safe and well tolerated and improved CFTR function as assessed by reductions in sweat chloride (SwCl) concentration [16] . A remaining question is whether tezacaftor/ivacaftor significantly impacts lung function in this age group.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, it was FDA‐approved for patients 6 to 11 years old based on an open‐label phase 3 study. The study demonstrated tolerance, reduced sweat chloride concentrations of −14.5 mmol/L, a relative change in ppFEV1 of 1.4%, maintenance of normal growth for age, and an increase in CFQ‐R respiratory domain of 3.4 points 35 . As seen with ivacaftor in a previously reviewed case series of 15 pancreatic sufficient adults with recurrent pancreatitis, those on ivacaftor who transitioned to tezacaftor/ivacaftor had a decrease in pancreatitis.…”
Section: Modulator‐specific Effectsmentioning
confidence: 73%